GAGASAN HUSBAND STITCH SEBAGAI TINDAK PIDANA KEKERASAN SEKSUAL DI INDONESIA - Nazilah Achmad (2024)
It started with a woman who shared her birth experience via her Twitter account, where she admitted that she received a husband stitch from the midwife who handled her birth. Husband stitch is an additional stitch given to women after vaginal delivery and is not part of an official medical procedure. In general, this kind of suture is performed without involving the patient's consent. From a health perspective, husband stitch does not provide any health benefits at all. According to the World Health Organization (WHO), this action includes the third type of female genital mutilation, namely infibulation. In Indonesia, until now there are no laws and regulations that regulate the prohibition of this issue. Meanwhile, regarding the practice of FGM itself, there are quite a lot of international policies that regulate the prohibition of this practice. Through this research, the author will examine the issue of husband stitch to be pursued as a criminal offense. Apart from that, the author will also use Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence as the ideal regulatory standard for the issues raised. The aim of this research is to find out how husband stitch regulations are in Law Number 12 of 2022 and the urgency for them to be regulated in these statutory regulations. Regarding research methods, the type of research the author uses is normative legal research, the problem approach used is the statute approach, and the data collection methods the author uses include library studies and interview techniques to complete the required data sources.